Sustaining peace in Ethiopia: The end of the war in the North should be the prelude to fundamental governance reforms - Gerrit Kurtz (Stiftung Wissenschaft und Politik (SWP), 2023)
The agreement signed by the Tigray People's Liberation Front (TPLF) and the Ethiopian government on 2 November 2022 offers a real chance to end one of the bloodiest wars in the world. The implementation of the agreement is going well so far. However, the peace process has brought into focus the question of a stable distribution of power within Ethiopia and in the Horn of Africa. The government under Prime Minister Abiy Ahmed faces three key challenges. First, it must integrate the TPLF and at the same time disengage from the partnership with Eritrea. Second, it must rebalance the domestic relationship between the main political actors in order to stop the escalating violence in the states of Amhara and Oromia. Finally, it must bring together a society divided and impoverished by war. International partners should support Ethiopia in addressing these challenges with conditional financial assistance and peacebuilding projects.
Keywords: 320; Äthiopien; Eritrea; Abiy Ahmed; Isaias Afwerki; Tigray; Amhara; Oromia; Afar; Tigray People's Liberation Front; TPLF; Ethiopian People's Revolutionary Democratic Front; EPRDF; Prosperity Party; Ethiopian National Defence Forces; ENDF; Tigray Defence Forces; TDF; Oromo Liberation Army; OLA; Fano; Afrikanische Union; Dürre; Hungersnot; Ethiopia; Eritrea; Abiy Ahmed; Isaias Afwerki; Tigray; Amhara; Oromia; Afar; Tigray People's Liberation Front; TPLF; Ethiopian People's Revolutionary Democratic Front; EPRDF; Prosperity Party; Ethiopian National Defence Forces; ENDF; Tigray Defence Forces; TDF; Oromo Liberation Army; OLA; Fano; African Union; drought